Edukasi Pencegahan Demam Berdarah Dengue di SDN 76 Abeli, Kota Kendari - Mubarak, Mubarak; Alifariki, La Ode; Kusnan, Adius (Indonesia Berdaya, 2022)
DHF is a disease caused by the dengue virus which is transmitted through the bite of the Aedes aegypti mosquito and enters the human bloodstream. This service aims to provide education for students about Dengue Hemorrhagic Fever Prevention at SDN 76 Abeli, Kendari City. This service method is health counseling, discussion and leaflet distribution which was carried out on June 13, 2022. This activity is in the form of health education about dengue disease to students at SDN 76 Abeli, Kendari City, involving 50 elementary school students. The result of this service is that students are very enthusiastic during the implementation of health counseling and also ask questions to the speaker. The conclusion of the service is that the health counseling method is effective in stimulating students to take action to prevent the incidence of dengue hemorrhagic fever. Abstrak: DBD adalah penyakit yang disebabkan oleh virus Dengue yang ditularkan melalui gigitan nyamuk Aedes Aegypti dan masuk ke peredaran darah manusia. Pengabdian ini bertujuan untuk memberikan edukasi bagi siswa tentang Pencegahan Demam Berdarah Dengue di SDN 76 Abeli, Kota Kendari. Metode pengabdian ini adalah penyuluhan kesehatan, diskusi dan pembagian leaflet yang telah dilaksanakan pada tanggal 13 Juni 2022. Kegiatan ini berupa pendidikan kesehatan tentang penyakit DBD pada siswa SDN 76 Abeli, Kota Kendari melibatkan 50 siswa Sekolah Dasar. Hasil pengabdian ini adalah siswa sangat antusias selama pelaksanaan penyuluhan kesehatan dan juga mengajukan pertanyaan kepada pamateri. Kesimpulan pengabdian bahwa metode penyuluhan kesehatan efektif dalam merangsang siswa untuk melakukan tindakan pencegahan kejadian demam berdarah dengue.